Hydride state accumulation in native [FeFe]-hydrogenase with the physiological reductant H2 supports its catalytic relevance. Issue 51 (7th June 2022) - Senger, Moritz; Kernmayr, Tobias; Lorenzi, Marco; Redman, Holly J.; Berggren, Gustav
Abstract : Studies of enzymatic catalysis often rely on non-biological reagents, which may affect catalytic intermediates and produce off-cycle states. Here the influence of buffer and reductant on key intermediates of [FeFe]-hydrogenase are explored. Abstract : Small molecules in solution may interfere with mechanistic investigations, as they can affect the stability of catalytic states and produce off-cycle states that can be mistaken for catalytically relevant species. Here we show that the hydride state (Hhyd ), a proposed central intermediate in the catalytic cycle of [FeFe]-hydrogenase, can be formed in wild-type [FeFe]-hydrogenases treated with H2 in absence of other, non-biological, reductants. Moreover, we reveal a new state with unclear role in catalysis induced by common low pH buffers.